Autonomous Vehicles in International Freight Transport: Future Prospects - Rahila Rahimli (Theoretical Hypotheses and Empirical Results, 2026)
Self-driving trucks, artificial intelligence, sophisticated sensor systems (LiDAR, radar), and 5G-enabled communication represent the forefront of autonomous vehicle technologies that are rapidly reshaping international freight transportation. These innovations are driving substantial improvements in productivity, reducing operating costs, enhancing overall safety, and ensuring the uninterrupted flow of cargo across long distances. The growing demand for faster, more reliable, and environmentally efficient logistics solutions, coupled with labor shortages in the trucking sector and increasing global trade volumes, is expected to accelerate the expansion of the worldwide autonomous truck industry dramatically over the next decade. This study’s main goal is to offer a thorough quantitative and qualitative evaluation of how autonomous vehicles affect the resilience and efficiency of international freight transit. The study uses a mixed-methods approach that includes expert interviews to gather useful insights from stakeholders, a comparative analysis of the World Bank’s Logistics Performance Index (LPI) to assess logistical improvements, an augmented gravity model of trade to quantify cross-country effects, and a systematic literature review to synthesize current academic and industry knowledge. The study focuses on worldwide trends and aims to draw broadly applicable conclusions in various infrastructure and economic scenarios. Leading nations like the US, China, Germany, and the Netherlands are used as examples, as are newly developed transit corridors that show how quickly autonomous technology are being adopted. These illustrations offer verifiable proof of the possible advantages and difficulties of autonomous freight transport. In order to facilitate the strategic integration of autonomous transport systems into current supply chains and promote sustainable, effective, and technologically advanced international logistics networks, the research’s findings are intended to provide governments, logistics companies, and international organizations with practical recommendations.